Longitudinal changes in patient‐reported outcomes after artificial urinary sphincter implantation. Issue 3 (13th April 2020) - Yokoyama, Minato; Masuda, Hitoshi; Ito, Masaya; Waseda, Yuma; Moriyama, Shingo; Toide, Masahiro; Uchida, Yusuke; Uehara, Sho; Kijima, Toshiki; Yoshida, Soichiro; Ishioka, Junichiro; Matsuoka, Yoh; et al.
Abstract: Objective: To evaluate the time course of lower urinary tract symptoms (LUTS) after artificial urinary sphincter (AUS) implantation based on individual longitudinal changes of patient‐reported outcomes. Methods: This retrospective study included 66 male patients with severe urinary incontinence who were treated with primary AUS implantation between 2009 and 2019. International Consultation on Incontinence Questionnaire‐Short Form (ICIQ‐SF) and International Prostate Symptom Score (IPSS) questionnaires were used to evaluate continence status and LUTS preoperatively, 1, 3, and 12 months after activation, and then annually. The annual changes in scores were calculated with a linear mixed model. Results: Of the 66 patients, 63 (95%) achieved complete or social continence (number of pads used ≤1/d) at 1 month after activation. Mean preoperative ICIQ‐SF, IPSS, and IPSS‐quality of life (QOL) score were 18.9, 14.9, and 5.4, respectively; the corresponding scores at 1 month after activation were 4.5, 9.0, and 1.7 (all P < .001), respectively. During the mean follow‐up period of 36 months, the annual changes in the scores from 1 month after activation were 0.51 ( P = .002), −0.30 ( P = .184), and 0.19 ( P < .001), respectively. As for individual IPSS items, while incomplete emptying, frequency, urgency, and weak stream improved significantly 1 month after activation, no significant changes from 1 month after activation were observed except for longitudinal deterioration of incomplete emptying score (0.08/y, P = .029). Conclusion: Continence status and QOL score markedly improved by AUS implantation immediately, but deteriorated over time. Improved LUTS were maintained without a worsening trend, however.